Digitizing Student Nutritional Status Monitoring through the Development of Anthropometric Applications: Longitudinal Studies of BMI and Abdominal Circumference - Fatmayanti Nawai; Mahyudin Bami; Nur Natalia H Uri; Irmariani Irbar; Ade Chairina (Indonesian Health Journal, 2026)
Student nutritional status is an important indicator in determining the health quality of young adults. Changes in lifestyle during the education period can affect students’ anthropometric conditions, particularly body mass index (BMI) and abdominal circumference. This study aimed to analyze changes in BMI and abdominal circumference among students of the Department of Nutrition over a one-year period without intervention and to develop an Android-based anthropometric application as a tool for monitoring nutritional status. The study used a longitudinal observational design with a paired-sample approach involving 106 students from the Department of Nutrition, consisting of the Diploma III Nutrition Program and the Bachelor of Applied Nutrition and Dietetics Program. Measurements were conducted in 2025 and repeated one year later, including body weight, height, abdominal circumference, and BMI. Data were analyzed using a paired sample test with a 95% confidence level.